Parámetros de desarrollo urbano sostenible en Bogotá, Colombia (2017)
This document establishes the parameters of sustainable urban development that should be considered for Bogota, in order to make a diagnosis of its current state. In the research project, the mechanisms for implementing sustainability in the urban field were initially identified in the most important cities of the world. Within these mechanisms, the criteria, parameters and restrictions were classified for the purpose of carrying out urban plans according to the situation in the city. Once the study of the international context was completed, it was investigated the most important advances in Colombia in relation to sustainable urbanism. The research then focused on determining whether those criteria, parameters, and restrictions applied to Bogota, aimed to encourage the sustainability of the city and, furthermore, to create future urban plans; in case they could not be implemented, strategies were proposed and validated with experts...